Urinary profiling of tryptophan and its related metabolites in patients with metabolic syndrome by liquid chromatography-electrospray ionization/mass spectrometry - Oh, Ji Sun; Seo, Hong Seong; Kim, Kyoung Heon; Pyo, Heesoo; Chung, Bong Chul; Lee, Jeongae (SPRINGER HEIDELBERG, 2017)
Tryptophan (Trp) is an essential amino acid that plays an important role in protein synthesis and is a precursor of various substances related to diverse biological functions. An imbalance in Trp metabolites is associated with inflammatory diseases. The accurate and precise measurement of these compounds in biological specimens would provide meaningful information for understanding the biochemical states of various metabolic syndrome-related diseases, such as hyperlipidemia, hypertension, diabetes, and obesity. In this study, we developed a rapid, accurate, and sensitive liquid chromatography-tandem mass spectrometry-based method for the simultaneous targeted analysis of Trp and its related metabolites of the kynurenine (Kyn), serotonin, and tryptamine pathways in urine. The application of the developed method was tested using urine samples after protein precipitation. The detection limits of Trp and its metabolites were in the range of 0.01 to 0.1 mu g/mL. The method was successfully validated and applied to urine samples from controls and patients with metabolic syndrome. Our results revealed high concentrations of Kyn, kynurenic acid, xanthurenic acid, and quinolinic acid as well as a high Kyn-to-Trp ratio (KTR) in patients with metabolic syndromes. The levels of urine Kyn and KTR were significantly increased in patients under 60 years old. The profiling of urinary Trp metabolites could be a useful indicator for age-related diseases including metabolic syndrome.
Keywords: KYNURENINE PATHWAY METABOLITES; TANDEM MASS-SPECTROMETRY; INDOLEAMINE 2,3-DIOXYGENASE; MULTIPLE NEUROTRANSMITTERS; CARDIOVASCULAR RISK; ACID; SEROTONIN; PLASMA; RAT; ATHEROSCLEROSIS